Inducing defects in 3.3 kV SiC MOSFETs by annealing after ion implantation and evaluating their effect on bipolar degradation of the MOSFETs. (5th November 2018) - Konishi, Kumiko; Fujita, Ryusei; Mori, Yuki; Shima, Akio
Abstract: Process-induced basal plane dislocations (BPDs) formed by annealing after aluminum ion implantation were investigated, and their effect on the bipolar degradation of body diodes in 3.3 kV SiC MOSFETs was evaluated. Contact resistance in the p+ region decreases with ion dose but increases with implantation temperature due to the formation of the recrystallized layer at SiC surface and difference of acceptor activation rates in high and low temperature implantation. In the case of high ion dose implantation at room temperature, contact resistance was of 1.3 × 10 −3 Ωcm 2 . However, process-induced BPDs formed with high ion dose implantation at room temperature, and could be suppressed with low ion dose or high implantation temperature. They were formed after activation annealing, and expanded to form stacking faults (SFs) under both continuous irradiation from a Hg lamp and current stress. Bipolar degradation occurred in the case of MOSFETs fabricated using high ion dose implantation at room temperature, but was not observed in the case of either low ion dose or high implantation temperature. The activation energy for SF expansion velocity in the ⟨1–100⟩ direction was estimated to be 0.20 eV at a forward current density of 125 A cm −2 . Moreover, the results of a long duration current stress test with high current density and high junction temperature indicate that low ion dose or high implantation temperature can suppress the formation of process-induced BPDs. MOSFETs fabricated using optimized ion implantation conditions show high reliability under bipolar operation.